Optimal perioperative anesthesia management for gynecologic interstitial brachytherapy - Nielsen, Alison A.; Liyanage, Tehani A.; Leiserowitz, Gary S.; Mayadev, Jyoti (Journal of Contemporary Brachytherapy, 2017)
Purpose : To propose an optimal perioperative pain management clinical care pathway for interstitial brachytherapy for gynecologic cancer based on our interdepartmental experience. Material and methods : We conducted a retrospective review of 23 women who underwent 32 interstitial brachytherapy procedures for gynecological cancers, analyzing patient demographics, type of anesthetic, medications, postoperative pain scores, adverse events, and delays in discharge. We measured the association of postoperative nausea and/or vomiting (PONV) with hydromorphone use, and postoperative pain scores and total narcotic administration with type of anesthesia. Results : In 91% of patients postoperative pain was managed with an epidural infusion plus, as needed (PRN), IV or patient controlled analgesia (PCA) narcotics. The most common postoperative adverse event was PONV (53%), followed by delirium (22%). Hospital discharge was delayed, at least by one night, in 26% of patients. Use of a basal rate on the PCA was associated with all cases of delayed discharge from over-sedation and PONV. The use of 5 mg or more of intravenous (IV) hydromorphone during the first 24-hours postoperatively was associated with PONV (p = 0.01). Use of a basal PCA was associated with delirium (p = 0.03). Postoperative pain scores were not significantly associated with the type of anesthesia. Conclusions : Interstitial gynecologic brachytherapy requires a multidisciplinary effort for optimal perioperative management. Our study outlines the appropriate preoperative, intraoperative, and postoperative anesthesia clinical care pathway. Decreased narcotic use during hospitalization and utilization of a patient-directed infusion may decrease side effects and allow for a more efficient hospital discharge.